Approaches for a comprehensive regulatory response to illegal gold commerce - Valverde Luna, Vanessa Sofía (2017)
This paper pretends to analyze the functioning and the limitations of some legal tools that the Peruvian state has posed as a part of his normative answer to the grave phenomenon of illegal gold mining, organized form of criminality whose utilities have surpassed the ones of drug trafficking. With this purpose, two axes of analysis has been proposed with incidence upon the illegal commercialization of gold: (i) the criminal tools, which specifically involve the crimes of illegal mining, clandestine commerce and money laundering; and (ii) the administrative tools, which involve the Legislative Decrees N° 1103 and 1107, the Supreme Decrees N° 012-2012-EM and N° 17-2009-MTC, among others. The authors have noticed several legislative policy errors in these elements and therefore implement recommendations to increase the global effectiveness of the regulation.